DNA extraction and PCR optimization of mitochondrial coi gene in the genus betta - Aisyah, Binti Shamsuddin (Universiti Malaysia Sarawak (UNIMAS), 2012)
Studies were conducted to study the optimization of the extraction of DNA and mitochondrial COl gene in two species of the genus Bella; Bella splendens and Betta unimaculata. A total of 15 individuals from Betta fish have been taken from Temerloh, UNIMAS campus, and several locations in Kuching as well as from local aquarium shops and wet markets. From optimization, eight individuals from 15 samples of Bella fish has been successfuny showed a single band. Various measures have been changed in the form of PCR temperature and time for each steps of PCR to identify the most effective parameters for the PCR product. Initial denaturation of the PCR parameters: 94°C for 3 minutes; annealing: 48.3°C for 1 minute; extension: 72 o C for 1.30 minutes; extension ends: 72 ° C for 5 minutes. 100bp DNA ladder was used to estimate the size of about 520 bp.